Never alone - Haynes, Elizabeth, 1971- (Myriad Editions, 2016)
"Sarah Carpenter lives with her two dogs in a farmhouse, high on the North Yorkshire moors. Alone for the first time since her husband died and her children left home, she isn't exactly lonely but welcomes the arrival of an old friend, Aiden Beck, who needs a place to stay. Aiden clearly has secrets, but then so does Sarah, and that's no reason not to respond to his warmth and charm. But something doesn't feel quite right. As the weather closes in, and snowfall blocks the roads, events take a dramatic turn and suddenly Sarah finds herself in terrible danger, unsure of who she can trust."--